TINGKAT SUKU BUNGA BANK KONVENSIONAL DAN KOMITMEN NASABAH MENABUNG DI BANK SYARIAH - Muchlis Yahya (University of Merdeka Malang, 2012)
banking. Shariah banking customers were divided into Moslem customers that only saved money at shariahbank (n1), Moslem customers that saved money both in shariah and conventional banks (n2), non-Moslemcustomers (n3). This study used primary data through questionnaires distributed to 400 people gotten from295.498 customers of shariah bank in Central Java. Then the customer data was analyzed by using logit model.For groups of customers n2 and n3, the interest rate had a significant negative effect on the commitment toinvest in shariah banks. However, for n1, the interest rate did not affect anything. n1 customers developedrelationship with shariah bank because of religion ideology motive. The result showed that n2, n3 customershad rational-economic mindset, whereas n1 customers had emotional-ideology mindset. This result showedthat shariah banking customers were dominated by customers that had rational-economic character. The openingof disagreement about the bank interest which was not usury and which was supported by only some socioreligiousorganizations like NU and Muhammadiyah could be an important factor the growth of Islamicbanking.